Pomiędzy narracją a tożsamością. Meandry autobiografii - Żardecka, Magdalena (Człowiek i Społeczeństwo, 2023)
The text is an analysis of interrelations binding autobiographical narration to individual and social identity. The first part tackles the fundamental connection between narration and individual, personal identity of the narrator – Paul Ricoeur, serving as a guide to this fundamental part of the proposed analysis, assumes that the narrative continuum follows and imitates the temporal continuum, constituting a flow in which it becomes possible to inscribe stories modifying and corroborating the reflected course of life. Conceptualizing and bringing to consciousness one’s course of life, auto-narration constitutes both a form of conscientious self-judgement and an occasion for self-deception. In the second part, the author attempts to show how auto narration and its significance for the individual identity changes, when it gets written down in the form of autobiography, subjected to the rigor of the writing and entering in complex interrelationships with social memory and identity. Here the author’s guides are among others Philippe Lejeune, Janet Verner Gunn and Georges Gusdorf. In the third part, the hitherto reconstructed structure of auto-narration and autobiography is destroyed: referring to such authors as Louis A. Renza, Jean Starobinski, John Sturrock, Michel Beaujour and Jacques Derrida, I demonstrate that the autobiographical undertaking is doubtful, and that the optimistic project of saving oneself by means of auto-narration and autobiography is an illusion. The presence of Derrida in the text is scarcely visible; yet it is Derrida, in dialogue with the late Ricoeur, that show us the way out from the autobiographical and identitary trap.